2017
DOI: 10.1002/mds.27038
|View full text |Cite
|
Sign up to set email alerts
|

Radiological biomarkers for diagnosis in PSP: Where are we and where do we need to be?

Abstract: PSP is a pathologically defined neurodegenerative tauopathy with a variety of clinical presentations including typical Richardson's syndrome and other variant PSP syndromes. A large body of neuroimaging research has been conducted over the past two decades, with many studies proposing different structural MRI and molecular PET/SPECT biomarkers for PSP. These include measures of brainstem, cortical and striatal atrophy, diffusion weighted and diffusion tensor imaging abnormalities, [18F] fluorodeoxyglucose PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
242
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 209 publications
(256 citation statements)
references
References 233 publications
(453 reference statements)
13
242
1
Order By: Relevance
“…These may be characterized by less severe or incomplete patterns, compared with typical and full-blown PSP. The panellists’ decision was consistent with both the EANM procedural guidelines [72] and the more recent diagnostic criteria of the Movement Disorder Society [5, 73], which support the use of FDG PET for discriminating PD from atypical parkinsonian syndromes.…”
Section: Discussionsupporting
confidence: 60%
“…These may be characterized by less severe or incomplete patterns, compared with typical and full-blown PSP. The panellists’ decision was consistent with both the EANM procedural guidelines [72] and the more recent diagnostic criteria of the Movement Disorder Society [5, 73], which support the use of FDG PET for discriminating PD from atypical parkinsonian syndromes.…”
Section: Discussionsupporting
confidence: 60%
“…At baseline, patients with PSP-RS showed a typical pattern of brain damage, including midbrain atrophy, prominent frontal cortical thinning (extended minimally to temporoparietal regions) and widespread WM involvement of the main infratentorial and supratentorial tracts that exceeded cortical damage 3. Longitudinal study showed that PSP-RS exhibited no further changes in cortical thinning, while midbrain atrophy and WM damage significantly progressed with a substantial impact on clinical decline.…”
Section: Discussionmentioning
confidence: 95%
“…Remarkable midbrain and cortical atrophy, usually involving the premotor and prefrontal regions, are typically observed in PSP-RS 3. More recently, extensive cortical thinning was found in the frontal, temporal, parietal and occipital cortex, cingulum, and insula in patients with PSP-RS compared with controls 4–6.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers (eg, genetic, epigenetic, or biochemical attributes) and imaging support 7 currently only serve to support a diagnosis of PSP and to exclude differential diagnoses. 4,7 Biomarkers and imaging may become available in the near future to define PSP subgroups on a neurobiological basis. Future insights in these areas may allow us to revise our proposed guidelines and maybe even the overall MDS-PSP criteria.…”
Section: Discussionmentioning
confidence: 99%